If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -3x) * 1 = 2(-4x + 7) Reorder the terms for easier multiplication: 3 * 1(1 + -3x) = 2(-4x + 7) Multiply 3 * 1 3(1 + -3x) = 2(-4x + 7) (1 * 3 + -3x * 3) = 2(-4x + 7) (3 + -9x) = 2(-4x + 7) Reorder the terms: 3 + -9x = 2(7 + -4x) 3 + -9x = (7 * 2 + -4x * 2) 3 + -9x = (14 + -8x) Solving 3 + -9x = 14 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 3 + -9x + 8x = 14 + -8x + 8x Combine like terms: -9x + 8x = -1x 3 + -1x = 14 + -8x + 8x Combine like terms: -8x + 8x = 0 3 + -1x = 14 + 0 3 + -1x = 14 Add '-3' to each side of the equation. 3 + -3 + -1x = 14 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 14 + -3 -1x = 14 + -3 Combine like terms: 14 + -3 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 5y+2=1(10y+4) | | 2(x-k)=2x+20 | | 4x^2+1x-2=0 | | 17x-2=18-3x | | 51(z-21)=-58 | | -8n-4=-2+6-7n | | 6(r-1)=-6+6r | | -15+-22=n | | -6p+6(5p+8)=128 | | p=2(74)+2(147) | | N+2= | | 13-x=x+11 | | -3=78 | | 3(2y-5)=21 | | 1/4(12-16q)=4(q+6) | | 10.8v=6t-.3t | | 7x+1+15x+10=2x+131 | | 20x+2=4(5x+1)-x+6 | | 3-9(x-1)-3=3+3(9-3x)-81 | | -2w^2+9w-13=0 | | 27-x=11 | | 5y-3+y+31=5y+40-3y | | -14n+12=-13n-10 | | -5(-2n+3)=-95 | | 20x+2=4(5x+1)-x+8 | | x+x+34+4x-37=819 | | 7n+5=75 | | -6x+14=12-8x | | 12+x=7 | | -15(-2)= | | (n+4)*7=56 | | x^2+16x-17=0 |